Metacognition, Attitude Towards Mathematics and Academic Performance of Grade - 9 Students in a District of Nueva Vizcaya - Yarcia, Lyrma; Nangpuhan, Desiree Gume (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the levels of metacognition, attitude toward mathematics, and academic performance of Grade 9 students in Nueva Vizcaya, as well as the relationships and predictive influence among these variables. Anchored on Flavell’s Theory of Metacognition (1976), Zimmerman’s Self-Regulated Learning Theory (2002), and Bandura’s Social Cognitive Theory (1986), the study adopted a quantitative approach using descriptive, comparative, correlational, and predictive research designs. Data were collected from Grade 9 students in public secondary schools through proportionate stratified random sampling. Standardized instruments, namely the Metacognitive Awareness Inventory (MAI), the Attitude Toward Learning Mathematics Scale (ATLM), and students’ mathematics grades, were utilized. Statistical analyses included descriptive statistics, repeated measures ANOVA, correlation analysis, and stepwise multiple regression. Findings revealed that students demonstrated a high level of metacognition but showed inconsistencies in reflective and evaluative practices. Students exhibited a neutral attitude toward mathematics, characterized by strong recognition of its value but moderate levels of enjoyment, confidence, and motivation. Academic performance was generally satisfactory to very satisfactory. Results further indicated a significant but weak positive relationship between metacognition and academic performance, no significant relationship between attitude and performance, and a moderate significant relationship between metacognition and attitude. Regression analysis showed that metacognition significantly predicts academic performance, whereas attitude does not, with the model explaining only a small proportion of variance. The study concludes that metacognition plays a more direct role in academic achievement, while attitude functions as a supportive factor. It recommends strengthening metacognitive strategies in instruction and exploring additional variables influencing performance. This study aligns with SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth) by promoting improved learning outcomes and competencies essential for future workforce readiness. It contributes to educational and socio-economic sustainability by informing instructional practices and policies that enhance both cognitive and affective dimensions of mathematics learning.